2010
DOI: 10.1515/cclm.2010.212
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the lipoxygenase derived lipid mediators in atherosclerosis: leukotrienes, lipoxins and resolvins

Abstract: Atherogenesis is an inflammatory process with leukocytes infiltrating the arterial intima. The lipoxygenase pathways play a role in leukocyte recruitment through the generation of two classes of arachidonic acid lipid mediators, the leukotrienes and the lipoxins, and one class of omega-3 fatty acid metabolites, the resolvins. There is evidence from animal studies and human genetic studies that the leukotrienes and the enzymes necessary for their generation play a role in atherosclerosis, and possibly even in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 140 publications
0
64
0
3
Order By: Relevance
“…Isoprostanes are a class of prostaglandin-like products formed via free-radical-mediated oxidation of arachidonic acid, esterified in membrane phospholipids. All these lipid mediators are consistently observed in atherosclerotic lesions where, together with the oxLDL-derived oxidized lipids, they contribute to the inflammatory responses and to plaque progression [228][229][230][231][232].…”
Section: Arachidonic Acid Derivatives In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Isoprostanes are a class of prostaglandin-like products formed via free-radical-mediated oxidation of arachidonic acid, esterified in membrane phospholipids. All these lipid mediators are consistently observed in atherosclerotic lesions where, together with the oxLDL-derived oxidized lipids, they contribute to the inflammatory responses and to plaque progression [228][229][230][231][232].…”
Section: Arachidonic Acid Derivatives In Atherosclerosismentioning
confidence: 99%
“…Leukotrienes (LTs) are generated from arachidonic acid by the 5-, 12-, and 15-LO pathways [232]. Several studies have suggested the existence of a potential link between the LT signaling cascade and the progression of atherosclerosis.…”
mentioning
confidence: 99%
“…Os produtos resultantes destas vias enzimáticas vão depender de quais são os tipos celulares que estão funcionando como alvos. 17,46 Os AGP ω3 são precursores de mediadores que incluem as resolvinas da série E (E1 ou RvE1: ácido 5S, 12R,18R-trihidroxi-6Z, 8E, 10E, 14Z, 16E eicosapentanóico / E2 ou RvE2: ácido 5S, 18 diidroxieiconadóide) que derivam dos EPA. Também são precursores das resolvinas da série D (D1 ou RvD1: ácido 7S, 8R, 17S-trihidroxi-4Z, 9E, 11E, 13Z, 15E, 19Z docosapentanóico / D2 ou RvD2: ácido 7S, 16R, 17S-trihidroxi-docosa-4Z, 8E, 10Z, 12E, 14E, 19Z hexaenóico) e suas formas epiméricas desencadeadas por Aspirina® derivadas de DHA, e as protectinas (PT)/ neuroprotectinas (NPD), também derivadas de DHA (Figura 2).…”
Section: Resolvinas E Protectinas Resolvinas E Protectinas Resolvinasunclassified
“…Além disso, sabe-se que mediadores derivados destes ω3 estão envolvidos na produção de resolvinas e protectinas, importantes na resolução da inflamação. 2,17 Os primeiros mediadores derivados do AA que foram descritos foram as LX, que exibem efeitos pró-inflamatórios e têm papel importante na resolução.…”
Section: Introdução Introdução Introdução Introduçãounclassified
“…Expression of the FPR2/ALX has been observed in several human chronic infl ammatory diseases, such as dermatitis, rheumatoid arthritis, and severe asthma, however, the role of the FPR2/ALX in atherosclerosis has not been investigated (3) .…”
mentioning
confidence: 99%